Stealing the Club from Hercules On Imitation in Latin Poetry - Conte, Gian Biagio (De Gruyter, 2017)
In this book, conceived as a sort of Prolegomena to his two Teubner editions, Conte gives account of his choices in editing his Virgilian text. Engaging in a passionate debate with his predecessors and critics, he guides the reader in a fascinating journey in the history of transmission and interpretation of Georgics and Aeneid and shows how lively textual criticism can be.